Introducing Micro-hardness Test in Forensic Odontology as an Aid in Solving Crimes: Multidisciplinary Approach - Kuldeep Singh Shekhawat1, Arunima Chauhan2, Manoj Varma3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Many studies have used dental radiography, light microscopy and electron microscopy to study the incinerated tooth for a possible estimation of temperature. However, no study so far has focused on measuring the change in hardness of dental hard tissue owing to higher temperatures. Objective: To introduce a novel method which may indicate the approximate temperature to which dental hard tissues (teeth) might have been exposed. Methods: We utilized Vickers hardness testing machine on a set of unrestored, non-carious extracted human teeth which were grouped and exposed to particular temperature of 200, 400, 600 and 800 degree Celsius respectively. Vickers Hardness Number (VHN) was obtained by measuring the diagonals formed after indentation at specific weight and time (constant) for all specimens in every group. Optical Photomicrography was used to view the enhanced images of indentation. The value was computed for all specimens in every group. Results: We observed overall reduction in VHN values with increase in specified temperature. VHN of enamel was limited to 200 and 400 degrees Celsius, whereas VHN for dentin greatly reduced at 600 and 800 degree Celsius by 10 times. Surprisingly, VHN values for enamel were higher for incinerated tooth (at 200 and 400 degrees Celsius) than VHN reported in literature for non-incinerated tooth. Conclusion: We suggest that micro-hardness test in forensic odontology is feasible and can be added in the list of already existing techniques for temperature estimation however, further experiments are recommended for its reproducibility.